Corob-x: a cooperative robot team for the exploration of lunar skylights - Dettmann, Alexander; Voegele, Thomas; Ocón, Jorge; Dragomir, Iulia; Govindaraj, Shashank; De Benedetti, Matteo; Ciarletti, Valerie; Hassen-Khodja, Rafik; Germa, Thierry; Viards, Raphael; Mantoani, Laura; Paz Delgado, Gonzalo Jesús (My University, 2022)
The project CoRob-X develops and demonstrates enabling technologies for multi-agent robotic teams to explore planetary surfaces with a focus on hard-to-reach areas where a collaborative scheme is required to efficiently explore complex environments. Exploring lava tubes is such a challenging environment and requires a team of robots able to collaborate in an autonomous way to find their way to the subsurface tube system, descend through a natural entry hole (the so-called skylight), and explore the interior with payload instruments to provide scientific data. The developed robotic exploration system that will tackle the ambitious goal is composed of three rovers with substantially different technical characteristics. The paper presents the overall approach, i.e., the control architecture, the robotic systems, and the software to be used. It also showcases the selected mission phases that will be demonstrated in a field-test campaign. In addition, a terrestrial mining use case is presented that demonstrates how the developed autonomy-enabling software can be transferred to terrestrial applications.
Keywords: Robótica; Espacio exterior; Luna; Robotics; Space; Moon